2022
DOI: 10.1186/s12889-022-12969-5
|View full text |Cite
|
Sign up to set email alerts
|

Willingness and uptake of the COVID-19 testing and vaccination in urban China during the low-risk period: a cross-sectional study

Abstract: Background Regular testing and vaccination are effective measures to mitigate the ongoing COVID-19 pandemic. Evidence on the willingness and uptake of the COVID-19 testing is scarce, and the willingness and uptake of vaccination may change as the pandemic evolves. This study aims to examine willingness and uptake of COVID-19 testing and vaccination during a low-risk period of the COVID-19 pandemic in urban China. Methods A cross-sectional online su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 62 publications
(23 reference statements)
2
7
0
Order By: Relevance
“…This finding aligns closely with findings from studies conducted in the USA, where the willingness rate was 69%, 40 in China with a willingness rate of 63.28% 41 and in Japan, where the corresponding figure was 65.7%. 42 …”
Section: Discussionsupporting
confidence: 90%
“…This finding aligns closely with findings from studies conducted in the USA, where the willingness rate was 69%, 40 in China with a willingness rate of 63.28% 41 and in Japan, where the corresponding figure was 65.7%. 42 …”
Section: Discussionsupporting
confidence: 90%
“…These disparities in testing could lead to underreporting and undetected community transmission of the SARS-CoV2 virus. 67 , 68 Some challenges in scaling the testing and diagnostic facilities for COVID-19 in SSA include gaps in service delivery and health systems, unskilled staffing, poor healthcare financing, sociocultural values, and the absence of infrastructure and technology to initiate and maintain diagnostic services. 69 71 This finding indicates the need for reform programs for strengthening and sustaining healthcare systems through appropriate health policy, adequate governmental focus and investment, and capacity-building in human resources, governance, and financing.…”
Section: Discussionmentioning
confidence: 99%
“…Due to different vaccination policies in different regions, the COVID-19 vaccination situation varies from region to region. An increasing number of studies have shown that there is a correlation between the prevalence of COVID-19 vaccination in different provinces in China and people's willingness to be vaccinated (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), but the willingness of residents to be vaccinated is not consistent across regions, which may be due to complex sociodemographics. Based on this, this study mainly conducted a meta-analysis on the associated factors of willingness to get COVID-19 vaccination in available studies, in order to evaluate the associated factors affecting people's willingness to vaccinate against COVID-19.…”
Section: Introductionmentioning
confidence: 99%